Making sense : conversations on consciousness, morality, and the future of humanity - Harris, Sam, 1967- (Ecco, an imprint of HarperCollins Publishers, 2020)
"A dozen of the best conversations from the podcast Making Sense, on topics that range from the nature of consciousness and free will, to politics and extremism, to acting ethically"--